2022
DOI: 10.3389/fcimb.2022.1002230
|View full text |Cite
|
Sign up to set email alerts
|

Streptolysin S targets the sodium-bicarbonate cotransporter NBCn1 to induce inflammation and cytotoxicity in human keratinocytes during Group A Streptococcal infection

Abstract: Group A Streptococcus (GAS, Streptococcus pyogenes) is a Gram-positive human pathogen that employs several secreted and surface-bound virulence factors to manipulate its environment, allowing it to cause a variety of disease outcomes. One such virulence factor is Streptolysin S (SLS), a ribosomally-produced peptide toxin that undergoes extensive post-translational modifications. The activity of SLS has been studied for over 100 years owing to its rapid and potent ability to lyse red blood cells, and the toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Streptolysin S, a peptide toxin generated by GAS, can induce lysis of red blood cells in humans, thereby conferring an advantage to the pathogen through the utilization of hemoglobin as a source of iron ( 19 ). Although the cytolytic capabilities of this pathogen have been studied for a century, the triggers and post-transcriptional mechanisms of toxin production remain elusive ( 20 ). In this case study, we focused on the triggers of streptolysin S genes’ expression where we constructed a co-expression network with default settings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Streptolysin S, a peptide toxin generated by GAS, can induce lysis of red blood cells in humans, thereby conferring an advantage to the pathogen through the utilization of hemoglobin as a source of iron ( 19 ). Although the cytolytic capabilities of this pathogen have been studied for a century, the triggers and post-transcriptional mechanisms of toxin production remain elusive ( 20 ). In this case study, we focused on the triggers of streptolysin S genes’ expression where we constructed a co-expression network with default settings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies have explored ways to inhibit SLS-mediated effects on host cells. Small molecule inhibitors of proteins involved in ion transport, such as DIDS (4,4’-diisothiocyanatostilbene-2,2’-disulfonate) and the N-cyanosulfonamide S0859 have been used to inhibit the lysis of erythrocytes and keratinocytes in response to SLS ( Higashi et al., 2016 ; Hammers et al., 2022 ). Interestingly, S0859 treatment was also able to prevent SLS-mediated NF-κB activation in keratinocytes, indicating that small molecule inhibition of the toxin can also prevent the associated damaging pro-inflammatory responses ( Hammers et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SLS is most well-known for its ability to rapidly lyse erythrocytes, which was traditionally attributed to the ability of the toxin to disrupt host membranes ( Duncan and Mason, 1976 ; Nizet et al., 2000 ; Carr et al., 2001 ). However, recent studies have indicated that SLS lyses host cells by targeting membrane proteins that are associated with ion transport ( Higashi et al., 2016 ; Hammers et al., 2022 ), and several reports have expanded the role of SLS in the context of Streptococcal infections. The toxin is known to play an important role in invasive GAS infections ( Betschel et al., 1998 ; Datta et al., 2005 ; Hirose et al., 2019 ), and is able to disrupt multiple host cells in addition to erythrocytes.…”
Section: Streptolysin Smentioning
confidence: 99%
See 1 more Smart Citation
“…SLS also targets and disrupts the function of multiple cell types including erythrocytes, macrophages, neutrophils, and keratinocytes [11][12][13][14]. Specifically, SLS has recently been shown to interact with ion transporters on the cell surface of erythrocytes and keratinocytes to induce cytotoxicity [15,16]. Furthermore, SLS can cause the disruption of the epithelial barrier through the degradation of tight junctions in vitro [17].…”
Section: Introductionmentioning
confidence: 99%